Health Effects of Intimate Partner Violence and Perception Regarding Minimization Strategies - Ghimire, Sailaja; Ghimire, Sushmita; Dahal Khatri, Bishal; Neupane , Sarala; Agrawal Sagtani , Resu; Upadhaya, Shambhu Prasad (Journal of Nepal Health Research Council, 2025)
Background: Intimate Partner Violence refers to any behavior within an intimate relationship that causes physical, psychological or sexual harm to those in the relationship. There are very serious health consequences in the health of women due to intimate partner violence. Thus, this study tries to explore the health effects of intimate partner violence and minimization strategies associated with it. Methods: A phenomenological study design was used in the study. Interviews were conducted among eleven study participants. Interviews were done with the survivors of violence, female community health volunteers, health personnel, local leaders, and staff of the municipality working in the Judicial Committee. Interviews were transcribed and translated and thematic analysis was done. Results: Survivors of violence mainly faced three forms of violence (Physical, sexual, and emotional) resulting in various health effects. Complaints like headache, head injury, pain, and sores were physical health effects reported by women whereas complaints like stress and having suicidal thoughts were the mental health effects. Family taboos, poverty, unemployment, illiteracy, social norms, and tradition were found to be the factors associated with intimate partner violence while the minimization strategies included proper communication, mutual understanding among partners, and awareness about social and legal rights. Conclusions: Effective communication and mutual understanding between husband and wife is key in reducing these health effects. In addition, in community level women empowerment is crucial for mitigating IPV. Keywords: Intimate partner violence; mental health; mitigation strategies; physical health.